Detection of SARS-CoV-2 antibodies formed in response to the BNT162b2 and mRNA-1237 mRNA vaccine by commercial antibody tests. Issue 39 (15th September 2021) - Kanji, Jamil N.; Bailey, Ashley; Fenton, Jayne; Ling, Sean H.; Rivera, Rafael; Plitt, Sabrina; Sligl, Wendy I.; Taylor, Sean; Turnbull, LeeAnn; Tipples, Graham; Charlton, Carmen L.
Abstract: Background: With rapid approval of SARS-CoV-2 vaccines, the ability of clinical laboratories to detect vaccine-induced antibodies with available high-throughput commercial assays is unknown. We aimed to determine if commercial serology assays can detect vaccine-induced antibodies (VIAs) and understand the vaccination response. Methods: This cohort study recruited healthcare workers and residents of long-term care facilities (receiving the BNT162b2 and mRNA-1273 products, respectively) who underwent serum collection pre-vaccination (BNT162b2 group), 2-weeks post vaccination (both groups), and pre-2nd dose (both groups). Sera were tested for the presence of SARS-CoV-2 IgG using four commercial assays (Abbott SARS-CoV-2 IgG, Abbott SARS-CoV-2 IgG II Quant, DiaSorin Trimeric S IgG, and GenScript cPASS) to detect VIAs. Secondary outcomes included description of post-vaccination antibody response and correlation with neutralizing titers. Results: 225 participants (177 receiving BNT162b2 and 48 receiving mRNA-1273) were included (median age 41 years; 66–78% female). Nucleocapsid IgG was found in 4.1% and 21.9% of the BNT162b2 (baseline) and mRNA-1273 (2-weeks post first dose). All anti-spike assays detected antibodies post-vaccination, with an average increase of 87.2% (range 73.8–94.3%; BNT162b2), and 25.2% (range 23.8–26.7%; mRNA-1273) between the first and last sampling time points (all p < 0.05). Neutralizing antibodies were detected at all post-vaccine timepoints for both vaccine arms, with increasing titers over time (all p < 0.05). Conclusions: Anti-spike vaccine-induced SARS-CoV-2 IgG are detectable by commercially available high-throughput assays and increases over time. Prior to second dose of vaccination, neutralizing antibodies are detectable in 73–89% of individuals, suggesting most individuals would have some degree of protection from subsequent infection.